Mechanical behaviour of salt : proceedings of the 7th Conference on the Mechanical Behavior of Salt, Paris, France, 16-19 April 2012 /: proceedings of the 7th Conference on the Mechanical Behavior of Salt, Paris, France, 16-19 April 2012. (©2012) - Unknown
No abstract available